Filling parameters and process optimization of mining–filling synergistic coal-based solid waste paste in Renjiazhuang mine - Li, Chao; Chen, Denghong; Yang, Ke (Frontiers in Materials, 2023)
In this paper, the authors address the issue of large solid waste output and surface subsidence in the western coal base. They focus on the 110904 filling working face of Renjiazhuang Mine and employ a combination of theoretical analysis, numerical simulation, and field practice to analyze the limit caving step and cycle pressure step of the working face. The authors propose a mining-filling coordination scheme called “three mining and one charging”. Through numerical simulation, they demonstrate that this scheme ensures the time-space continuity of the mining-filling cycle and is theoretically feasible. Additionally, the authors conduct nine groups of orthogonal simulation tests to identify the main factors affecting the filling effect. They conclude that the filling rate is the primary controlling factor, and there is a positive correlation between the filling rate and 1-day strength. The authors implement hanging pipe filling in the return air roadway of the 110904 working face, achieving a filling material 1-day strength of 2 MPa and a filling ratio of 80%. The mining-filling synergy scheme proves effective and feasible. However, the issue of pipe plugging during the filling process requires further optimization of the particle gradation in the subsequent filling material ratio scheme. Overall, the proposed mining-filling collaborative process serves as a theoretical reference for similar filling faces.